Correlation of serum homocysteine levels and hyperinsulinaemia with body mass index in polycystic ovarian syndrome - Rashmi Bhushan; Parul Sinha (Wolters Kluwer Medknow Publications, 2022)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies affecting women in reproductive age group. The interrelationship of serum homocysteine, homoeostatic assessment of insulin resistance (HOMA-IR) and body mass index amongst overweight, obese and non-obese PCOS patients is not fully established. Aims: We aimed to study the correlation of serum homocysteine levels and hyperinsulinaemia with body mass index (BMI) in PCOS patients. Study Setting and Design: This was a case-control study in which 35 women with PCOS and 35 non-PCOS women acting as controls were enrolled. Materials and Methods: Cases were identified by Rotterdam's criteria. (IR) indices, HOMA determination and serum homocysteine levels were determined and their correlation with BMI was studied. Statistical Analysis Used: Student's t-test and analysis of variance test were used for statistical analysis. The Pearson correlation coefficient was then used to estimate the correlation. Results: On overall evaluation, a significant positive correlation of fasting insulin, HOMA-IR and serum homocysteine) was observed (P < 0.05), however, on evaluating the correlation of these markers independently in cases and controls, only fasting insulin and HOMA-IR showed a significant correlation. In a multivariate model where PCOS was considered a dependent variable with age, fasting glucose, HOMA-IR, serum homocysteine and body mass index as the independent variables, only serum homocysteine levels were found to be significantly associated with the dependent variable (odds ratio = 1.172; 95% confidence interval = 1.032-1.330). Conclusion: PCOS women had significantly higher mean fasting glucose, fasting insulin, HOMA-IR and homocysteine levels as compared to non-PCOS controls. Mean HOMA-IR, homocysteine and fasting insulin levels showed a significant incremental trend with increasing BMI category in overall evaluation as well as in cases and controls independently.